Flexible glass and preparation method thereof

By adjusting the Si/O ratio, Li2O and P2O5 ratio in the flexible glass raw material components, and adding phosphorus pentoxide during the chemical strengthening process, the problem of insufficient strength and performance of flexible glass is solved, and the effect of improving the flexibility and bending performance of glass is achieved, while improving production safety and efficiency.

CN119569332AActive Publication Date: 2025-03-07XIANNING NANBO PHOTOELECTRIC GLASS CO LTD +1
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411511755.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-03-07
Estimated Expiration
2044-10-28

AI Technical Summary

Technical Problem

Existing flexible glasses still cannot meet most application scenarios in terms of strength and performance, and existing chemical reinforcement methods are cumbersome and inefficient.

Method used

By adjusting the Si/O ratio, Li2O and P2O5 ratio in the raw material components, and adding phosphorus pentoxide during the chemical strengthening process, the stress layer depth and ion exchange efficiency of the glass are increased, thereby improving the flexibility and bending performance of the glass.

Benefits of technology

It has achieved the improvement of the stress layer depth and ion exchange efficiency of flexible glass, improved the flexibility and bending performance of glass, reduced the chemical strengthening temperature, and improved production safety and efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses flexible glass and a preparation method thereof, and the flexible glass is prepared from the following raw materials in percentage by weight: 259.5%-64% of SiO2, 22%-24.8% of Al2O3, 0.1%-2% of P2O5, 0.1%-2% of ZrO2, 0.1%-2.5% of MgO, 3.5%-6.5% of Na2O, 0-1.1% of K2O, 3.5%-4.4% of Li2O, 3%-4.2% of B2O3 and 0.1%-0.3% of ZnO. The preparation method comprises the steps of founding, forming, chemical thinning, flattening treatment and chemical strengthening, wherein P2O5 is added into chemical strengthening molten salt. The Si / O ratio and the proportion of Li2O and P2O5 in the raw material components are adjusted, and phosphorus pentoxide is added in chemical strengthening, so that the stress layer depth and the ion exchange efficiency of the flexible glass are increased, and the flexibility of the glass is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of flexible glass, and in particular relates to flexible glass and a preparation method thereof. Background Art

[0002] Flexible glass refers to a bendable and flexible glass with good chemical stability, excellent surface and optical quality, and light weight. Therefore, it has been widely used in many fields such as flexible display, OLED lighting, and photoelectric conversion in recent years. However, flexible glass is not only a flexible material, but also a brittle material. Due to its extremely low thickness, microcracks and other defects on the glass will have a greater impact on its handling strength, making it easier to break than ordinary glass. Therefore, its strength and performance still cannot meet most application scenarios.

[0003] At present, the strength of flexible glass is mainly improved through the following technical solutions. First, through component design, the glass microstructure is made more stable, thereby improving the strength of the base glass; second, the processing technology is optimized, and a combination of mechanical grinding and chemical thinning is used to reduce surface defects of ultra-thin flexible glass and improve surface quality; finally, the surface compressive stress of the glass body is increased through chemical strengthening, so that it can inhibit the expansion of microcracks on the glass surface, thereby improving the bending strength and impact strength of the flexible glass.

[0004] Chinese patent CN114656142B discloses a flexible glass and its preparation method. The weight ratio of raw materials used in the flexible glass is: 60.04-63.01 parts by weight of silicon dioxide, 16.7-21.5 parts by weight of aluminum oxide, 12.93-19.85 parts by weight of boron oxide, 2.43-14.19 parts by weight of calcium carbonate, 0.16-2.07 parts by weight of magnesium oxide, 0.5-2.74 parts by weight of strontium carbonate, and 0.12-4.16 parts by weight of barium nitrate. The preparation method is to melt the glass, draw a tube in a polar atmosphere, and cut it to obtain the flexible glass. However, it does not contain lithium oxide, the chemical tempering time is long, and the conditions for glass molding are harsh, which has high requirements for the production environment.

[0005] Chinese patent CN118324427A discloses a chemical strengthening method for ultra-thin flexible glass, which first tempers the glass sample to be processed and then micro-etches it with HF etching solution, and finally performs a second tempering treatment to obtain ultra-thin flexible glass, which improves the appearance of the product while ensuring the product tempering stress value and other conditions, and simplifies the operation process, which is shorter and more efficient than traditional tempering conditions, and improves production capacity and product yield. However, the chemical strengthening steps are relatively cumbersome, and a large amount of HF etching solution is required to complete chemical thinning.

[0006] Chinese patent CN114262163A discloses a chemical strengthening method for inhibiting microcracks on the surface of flexible glass, which uses nano-scale silicon dioxide, dispersants, base materials, etc. to prepare transparent film materials, then solidifies them on the surface of flexible glass by laser evaporation, and finally performs chemical strengthening to obtain chemically strengthened flexible glass with surface coating, which effectively inhibits the generation and spread of cracks on the glass surface, improves the efficiency of chemical strengthening, and improves the strength of glass. However, it requires additional coating steps and film materials, and cannot increase the depth of chemical strengthening.

[0007] The existing technology mainly uses aluminum-silicon glass or lithium aluminum-silicon glass as the base glass, but the chemical strengthening ability of these two types of glass is limited and there is still room for improvement; in addition, the use of potassium nitrate salt bath for chemical strengthening or the use of sodium nitrate and potassium nitrate salts for two-step strengthening have limited effect on the strengthening stress improvement of the finished flexible glass, and there is no obvious gain in the bending performance of the flexible glass. Therefore, it is necessary to develop a flexible glass with high chemical strengthening ability and optimize the chemical strengthening method to improve the performance of the flexible glass. Summary of the invention

[0008] In response to the above technical problems, the present invention provides a flexible glass and a preparation method thereof. By adjusting the Si / O ratio, the proportion of Li2O and P2O5 in the raw material components, and adding phosphorus pentoxide to the chemically strengthened molten salt, the stress layer depth and ion exchange efficiency of the flexible glass are increased, thereby improving the flexibility of the glass.

[0009] In order to achieve the above-mentioned object, the present invention provides a flexible glass, which is composed of the following raw materials, measured by weight percentage: SiO2 59.5-64%, Al2O3 22-24.8%, P2O5 0.1-2%, ZrO2 0.1-2%, MgO 0.1-2.5%, Na2O 3.5-6.5%, K2O 0-1.1%, Li2O 3.5-4.4%, B2O3 3-4.2%, and ZnO 0.1-0.3%.

[0010] Preferably, the thickness of the flexible glass is ≤0.025 mm.

[0011] The present invention also provides a method for preparing flexible glass, comprising the following steps: (1) Melting: After iron removal and concentration of quartz sand, magnesite and smithsonite, they are mixed with other raw materials and melted at 1580-1660℃ for 5-8h to obtain glass liquid; (2) Molding: Molding and annealing the glass liquid to prepare the precursor glass; (3) Chemical thinning: placing the precursor glass in a chemical thinning solution for thinning to obtain thinned flexible glass; (4) Flattening: Cut the thinned flexible glass and flatten it; (5) Chemical strengthening: The flattened glass is preheated and then placed in molten salt for chemical strengthening, and then slowly cooled to obtain flexible glass. Preferably, the annealing temperature in step (2) is 650-670° C., and the annealing time is 30-60 min.

[0012] Preferably, the thickness of the precursor glass in step (2) is ≤0.15 mm.

[0013] Preferably, the preparation method of the chemical thinning liquid described in step (3) is: diluting the sulfuric acid solution and mixing it with the hydrofluoric acid solution to obtain the chemical thinning liquid.

[0014] Further preferably, the volume concentration of the sulfuric acid solution is 50%, the dilution factor is 25 times, the volume concentration of the hydrofluoric acid solution is 50%; and the volume ratio of the sulfuric acid solution to the hydrofluoric acid solution is 1:1.

[0015] Preferably, the molten salt in step (5) is composed of NaNO3, KNO3, and P2O5; the chemical strengthening temperature is 300-400°C, and the time is 10-20 min.

[0016] Further preferably, the weight percentage of NaNO3, KNO3, and P2O5 is 50:40-45:5-10.

[0017] Preferably, the preheating temperature in step (5) is 300-330°C, and the preheating time is 100-140 min; the slow cooling temperature is 350-380°C, and the slow cooling time is 90-120 min.

[0018] The beneficial effects of the present invention are: 1. By controlling the Si / O ratio between 2-3.5, the three-dimensional network structure formed by SiO4 tetrahedrons connected by bridging oxygen and the three-dimensional network structure formed by non-bridging oxygen bonding in the internal structure of the glass are formed. The existence of the bridging oxygen bonding structure ensures the low thermal expansion coefficient and good light transmittance of the glass, while the existence of non-bridging oxygen weakens the strength of part of the silicon-oxygen bonding, which reduces the melting point of the glass, reduces the viscosity, and facilitates large-scale production.

[0019] 2. Adjust the ratio of Li2O and P2O5 in the flexible glass raw material formula, so as to regulate the bond breaking and fluxing effect of Li2O and the ability of phosphorus oxygen tetrahedron [PO4] to form a glass network structure, thereby improving the exchange efficiency and ion exchange depth of the glass body during the ion exchange process, and thus improving the chemical strengthening ability of the original high-aluminum and lithium aluminum silicon glass. At the same time, the presence of Li2O and P2O5 can effectively reduce the thermal expansion coefficient of the glass, help improve the heat resistance of the glass, and ensure the dimensional stability during the subsequent high-temperature processing; in addition, Li2O and P2O5 can form tiny bubbles during the high-temperature melting process of the glass, which helps to remove bubbles in the glass liquid, making the glass more transparent and pure, and improving the optical transmittance of the finished glass. P2O5 has hygroscopicity and dehydration. The mixed use of the two can effectively avoid excessive reaction of Li2O with water vapor in the environment to cause deliquescence, thereby affecting the deviation of the actual amount of lithium oxide introduced into the batch.

[0020] 3. During the chemical strengthening process, sodium nitrate, potassium nitrate and phosphorus pentoxide are mixed in a certain proportion as molten salt, in which the content of phosphorus pentoxide is maintained between 5-10wt%, which improves the exchange efficiency of flexible glass during the ion exchange process; at the same time, due to the phosphorus pentoxide-doped salt bath, the stress layer depth of the glass can be increased during the strengthening process, and the flexibility of the glass is improved, thereby enhancing its bending performance.

[0021] 4. Limited by the boiling point of phosphorus pentoxide of 360°C, the salt bath temperature is designed to be lower than 360°C. Compared with the existing technology, the lower chemical strengthening temperature can significantly improve the operating safety of the tempering furnace and reduce the energy consumption of the equipment. DETAILED DESCRIPTION

[0022] The technical solution of the present invention is further explained below in conjunction with specific embodiments. It is worth noting that the following embodiments are only preferred embodiments of the present invention and should not be construed as limiting the present invention. The protection scope of the present invention shall be subject to the contents recorded in the claims. Any modification or replacement made by a person skilled in the art to the technical solution of the present invention without creative work shall fall within the protection scope of the present invention.

[0023] Examples 1-10, Comparative Examples 1-4 (1) Melting: After iron removal and concentration of quartz sand, magnesite and smithsonite, the mixture is mixed with feldspar, heavy soda ash, lithium carbonate, potassium carbonate, baddeleyite and other raw materials in proportion, and melted at 1580°C for 8 hours to obtain glass liquid. The mixing amounts of the raw materials are shown in Table 1. (2) Molding: The glass liquid is molded using a slit-down draw process with a molding thickness of 0.15 mm, and then annealed at 650°C for 60 minutes to obtain a precursor glass; (3) Preparation of chemical thinning solution: Pour 1L of 50% sulfuric acid into 25L of pure water and mix thoroughly to obtain mixed solution A. Pour mixed solution A into 1L of 50% hydrofluoric acid and mix thoroughly to obtain chemical thinning solution. (4) Chemical thinning: placing the precursor glass in a chemical thinning liquid for chemical thinning to obtain a thinned flexible glass with a thickness of 0.025 mm; (5) The edge of the flexible glass is thinned by laser cutting and flattened to obtain a size of 170×140×0.025 mm (length×width×thickness); (6) A group of 10 thinned flexible glasses after flattening were gently placed in a chemical strengthening jig, and then the jig together with the flexible glass substrate was placed in a chemical strengthening preheating furnace, preheated at 300°C for 110 min, and then placed in a molten salt of NaNO3 and KNO3 (50wt%:50wt%) that had been precipitated for 8 hours, and chemically strengthened at 350°C. After 16 minutes, the jig together with the flexible glass was transferred to a slow cooling furnace, slowly cooled at 360°C for 120 min, and then cooled to room temperature to obtain the flexible glass.

[0024] Table 1 Formula of flexible glass

[0025] Result detection: The FSM-6000LE tempered glass surface stress meter was used to measure the surface stress (CS) and stress layer depth (DOL) of the tempered glass. The data of 5 positions in the middle and four corners of the two surfaces of the sample were measured, and the average value was recorded. The QVS laser flatness measuring instrument of the Jiateng Instrument was used to measure 4 data at the center positions of the four sides of the two surfaces of the sample, and the average value was recorded. The Keyence IM-8000 was used to measure the bending radius of the sample, and the average value was recorded. In addition, if the glass breaks during the strengthening process, the breakage ratio was recorded.

[0026] Table 2 Effect of formulation on properties of flexible glass

[0027] The results show that when the mass ratio of Li2O and P2O5 in the raw materials is controlled at 2-3:1, the bond-breaking and fluxing effects of Li2O and the ability of phosphorus-oxygen tetrahedron [PO4] to form a glass network structure can be regulated, thereby improving the exchange efficiency and chemical strengthening depth of the glass during the chemical strengthening process.

[0028] Examples 11-12, Comparative Examples 5-14 (1) Melting: After iron removal and concentration of quartz sand, magnesite and smithsonite, the mixture is mixed with feldspar, heavy soda ash, lithium carbonate, potassium carbonate, baddeleyite and other raw materials in proportion, and melted at 1660° C. for 5 h to obtain glass liquid; wherein the mixing amounts of the raw materials are the same as those in Example 5; (2) Molding: The glass liquid is molded using a slit-down draw process with a molding thickness of 0.15 mm, and then annealed at 670°C for 30 minutes to obtain a precursor glass; (3) Preparation of chemical thinning solution: Pour 1L of 50% sulfuric acid into 25L of pure water and mix thoroughly to obtain mixed solution A. Pour mixed solution A into 1L of 50% hydrofluoric acid and mix thoroughly to obtain chemical thinning solution. (4) Chemical thinning: placing the precursor glass in a chemical thinning liquid for chemical thinning to obtain a thinned flexible glass with a thickness of 0.025 mm; (5) The edge of the flexible glass is thinned by laser cutting and flattened to obtain a size of 170×140×0.025 mm (length×width×thickness); (6) After flattening, 10 pieces of thinned flexible glass are gently placed in a chemical strengthening jig as a group, and then the jig together with the flexible glass substrate is placed in a chemical strengthening preheating furnace. After preheating, they are placed in molten salt for chemical strengthening. Then, the jig together with the flexible glass is transferred to a slow cooling furnace, and then slowly cooled to room temperature to obtain the flexible glass.

[0029] Table 3 Preheating, chemical strengthening and slow cooling conditions

[0030] Note: Na represents NaNO3, K represents KNO3, P represents P2O5; IOX1 represents the first chemical strengthening, and IOX2 represents the second chemical strengthening.

[0031] Table 4 Effect of preparation conditions on the properties of flexible glass

[0032] The results show that mixing sodium nitrate, potassium nitrate and phosphorus pentoxide in a certain proportion during chemical strengthening can improve the exchange efficiency of flexible glass during the ion exchange process. Due to the phosphorus pentoxide doped salt bath, the stress layer depth of the glass can be increased during the strengthening process, and the flexibility of the glass is improved, thereby enhancing its bending performance. At the same time, due to the boiling point of phosphorus pentoxide being 360°C, the salt bath temperature is designed to be lower than 360°C. Compared with the existing technology, the lower chemical strengthening temperature can significantly improve the operating safety of the tempering furnace and reduce the energy consumption of the equipment.

Claims

1. A flexible glass, characterized in that: Calculated by weight percentage, it is composed of the following raw materials: SiO2 59.5-64%, Al2O3 22-24.8%, P2O5 0.1-2%, ZrO2 0.1-2%, MgO 0.1-2.5%, Na2O 3.5-6.5%, K2O 0-1.1%, Li2O 3.5-4.4%, B2O3 3-4.2%, and ZnO 0.1-0.3%.

2. The flexible glass according to claim 1, characterized in that: The thickness of the flexible glass is ≤0.025 mm.

3. A method for preparing the flexible glass according to any one of claims 1 to 2, characterized in that: The steps include: (1) Melting: Mix the raw materials and melt them at 1580-1660℃ for 5-8h to obtain glass liquid; (2) Molding: Molding and annealing the glass liquid to prepare the precursor glass; (3) Chemical thinning: placing the precursor glass in a chemical thinning solution for thinning to obtain thinned flexible glass; (4) Flattening: Cut the thinned flexible glass and flatten it; (5) Chemical strengthening: The flattened glass is preheated and then placed in molten salt for chemical strengthening, and then slowly cooled to obtain flexible glass.

4. The preparation method according to claim 3, characterized in that: The annealing temperature in step (2) is 650-670° C., and the annealing time is 30-60 min.

5. The preparation method according to claim 3, characterized in that: The thickness of the precursor glass in step (2) is ≤0.15 mm.

6. The preparation method according to claim 3, characterized in that: The preparation method of the chemical thinning liquid described in step (3) is: dilute the sulfuric acid solution and mix it with the hydrofluoric acid solution to obtain the chemical thinning liquid.

7. The preparation method according to claim 6, characterized in that: The volume concentration of the sulfuric acid solution is 50%, the dilution factor is 25 times, the volume concentration of the hydrofluoric acid solution is 50%, and the volume ratio of the sulfuric acid solution to the hydrofluoric acid solution is 1:

1.

8. The preparation method according to claim 3, characterized in that: The molten salt in step (5) is composed of NaNO3, KNO3, and P2O5; the chemical strengthening temperature is 300-400°C, and the time is 10-20 minutes.

9. The preparation method according to claim 8, characterized in that: The weight percentage concentration ratio of NaNO3, KNO3 and P2O5 is 50:40-45:5-10.

10. The preparation method according to claim 3, characterized in that: The preheating temperature in step (5) is 300-330°C, and the preheating time is 100-140 minutes; the slow cooling temperature is 350-380°C, and the slow cooling time is 90-120 minutes.

Citation Information

Patent Citations

  • Chemical strengthening method for inhibiting microcracks on surface of flexible glass

    CN114262163A

  • Flexible glass and preparation method thereof

    CN114656142B

  • Chemical strengthening method of ultrathin flexible glass

    CN118324427A

  • Glass composition and strengthening method thereof

    CN108101362A

  • Lithium aluminosilicate glass and preparation method thereof

    CN108863050A